Exposure to Lead (Pb) influences the outcomes of male-male competition during precopulatory intrasexual selection - Rosemary Patrick; Kim Colyvas; Andrea S. Griffin; Michael Stat; Wayne A. O’Connor; Mohammad Mahmudur Rahman; Mallavarapu Megharaj; Geoff R. MacFarlane (Scientific Reports)
Abstract Male-male competition is a component of Darwin’s theory of precopulatory intrasexual selection, where males compete for access to resources important for reproduction and successful males pass on traits that endow greater competitive ability to their offspring, thereby exaggerating the trait(s) over evolutionary time. Metals, such as lead (Pb) often occur in urban mangrove forests, where shore crabs reside, and being neurotoxic may cause sub-lethal effects on behaviour. In this study, we asked whether exposure to Pb influences the outcomes of male-male competition in the Semaphore crab, Heloecius cordiformis, thereby altering outcomes of intrasexual selection. Crabs were exposed to an environmentally relevant, and a behaviourally relevant, concentration of lead (i.e. Pb, 10 µg/L and 100 µg/L respectively) under laboratory conditions for 96 h and subsequently allowed to compete for burrow ownership in experimental arenas. Exposed crabs (100 µg/L) were less successful than control crabs in chela size-matched paired competitive interactions, spent less time in burrows and predominantly lost burrow ownership. Further, exposure to Pb contamination (both 10 µg/L and 100 µg/L) negated the chela size advantage in size-asymmetric competitive interactions. This contaminant-induced loss of size-related competitive advantage may result in relaxation in selection pressure on body size and smaller male carapace widths and especially male chela lengths in contaminated locations. Assessment of a range of locations in the wild found a consistent pattern of metal-associated size declines in more contaminated locations for males, but not for females.